Process for producing wax ester from dihydroxy fatty acid - Basri, Mahiran; Awang, Roila; Ahmad, Salmiah; Salleh, Abu Bakar (2009)

(untitled)
A process for producing wax ester comprising of esterifying dihydroxy fatty acied preferably dihydroxystearic acid with at least one alcohol in the presence of lipase as a catalyst which is then remove by filtration. The filtered catalyst could be reuse and provides a number of cost advantanges. In the preferred embodiment of the present invention, the dihydroxystearic acid is derived from palm based oleic acid and the alcohol contains 8 to 18 carbon atoms per molecules.